Comparison of Derivative Action Regulations in Indonesia and South Korea in Providing Legal Protection for Minority Shareholders - Putri, Melisa Dwi; Al Farisi, Muhammad Fahmi Reksa (Istinbath : Jurnal Hukum, 2024)
The board of directors can harm the interests of minority shareholders considering that shareholders are passive parties who do not participate in managing the company, thus there is a possibility of infringing upon the rights of the shareholders. A derivative action is a lawsuit by a shareholder on behalf of and representing the corporation against members of the board of directors who have made mistakes that resulted in losses to the corporation. Derivative action plays an important role in providing balanced protection for minority shareholders. The purpose of the research is to find a comparison of the regulation of derivative actions in Indonesia and South Korea in providing legal protection for minority shareholders. The research methodology uses a normative juridical method with a comparative research type. The research results indicate that the quality of protection for minority shareholders can be seen based on the jurisdiction of each country, which is rooted in the system used by that country. The fundamental difference between derivative action in Indonesia and Korea is that South Korean law has regulations regarding public shareholders who can file derivative lawsuits, with the requirement that they must have been shareholders for at least 6 consecutive months. In contrast, Indonesia does not have any regulations regarding this matter.